2016
DOI: 10.1162/rest_a_00566
|View full text |Cite
|
Sign up to set email alerts
|

Survive Another Day: Using Changes in the Composition of Investments to Measure the Cost of Credit Constraints

Abstract: Abstract-We introduce a novel empirical strategy to measure the size of credit shocks. Theoretically, we show that credit shocks reduce the value of long-term relative to short-term investments. Empirically, we can therefore compare the reduction of long-term relative to short-term investments within firms, allowing for firm-times-year fixed effects. Using Spanish firmlevel data, we estimate the credit crunch to be equivalent to an additional tax rate of around 11% on the longest-lived capital. To pin down cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 51 publications
3
41
0
Order By: Relevance
“…Based on our sample of listed manufacturing firms, we find that increasing Chinese import competition reduced the most durable investments more than the least durable investments. The estimated economic significance of our estimates compares to the effect that Garicano and Steinwender () estimate for the financial crisis on investment of Spanish firms…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Based on our sample of listed manufacturing firms, we find that increasing Chinese import competition reduced the most durable investments more than the least durable investments. The estimated economic significance of our estimates compares to the effect that Garicano and Steinwender () estimate for the financial crisis on investment of Spanish firms…”
Section: Introductionmentioning
confidence: 80%
“…As short‐term investments depreciate earlier, net investments tend to fall, and firms need to refinance more frequently . The literature has identified that credit crunches, uncertainty, investor pressures, or agency problems can be causal for short‐term investment behavior (see Aghion et al., ; Garicano and Steinwender, ; Terry, ; Garicano and Rayo, ; Bénabou and Tirole, ). In this article, we put forward another reason for corporate short‐termism: we argue that foreign competition can induce firms to distort investments away from assets that pay off in the distant future toward short‐term assets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While their study is based on firm balance sheet data, I additionally make use of loan-level data containing detailed information on the maturity and expiration dates of individual loan facilities. Similar identification ideas have recently also been employed by Duval, Hong, and Timmer (2017) and Garicano and Steinwender (2016). not only negatively impact the supply of bank credit and the cost of bond finance, but also the commercial paper market (Kacperczyk and Schnabl, 2010) and firms' costs of issuing equity (Belo, Lin, and Yang, 2014).…”
Section: Non-technical Summarymentioning
confidence: 86%
“…But, as Reinhart and Rogo (2009) note, there is no denitive evidence on the causal eects. The natural experiment 3 Gan (2007); Khwaja and Mian (2008); Amiti and Weinstein (2011); Garicano and Steinwender (2013) ;Bentolila et al (2015); Paravisini et al (2015) present further evidence.…”
mentioning
confidence: 87%